SUKUK MUDHARABAH SEBAGAI INSTRUMEN KEUANGAN ISLAM IDEAL KONTEMPORER - alimin, alimin (Al Qalam, 2013)
The year 2012 and 2013 can be regarded as the mudaraba sukuk revival since winning number and the value as compared to previous years. Indonesian mudaraba sukuk attract Islamic financial worlds' attention, because he was the first Indonesian sukuk while abroad is more aitively issuing ijara sukuk. In addition, it is identified that the Indonesia mudaraba sukuk is very attractive to investors and seem to be consistent and honest, but why ultimately mudaraba sukuk like abandoned? Actually, the more appropriate format for sukuk is mudhrabah while it is difficult to be applied in Islamic banking. Indonesia mudaraba sukuk application is quite phenomenal because it provides a very high return even once reached 24.3%, the highest return compared to all the world's sukuk and more Islamic and even more consistent in many ways. However, according to the application in general, mudaraba sukuk is still not consistent in terms of Shariah compliance, such as providing income and principal guarantees. Further, the fluctuation phenomenon of use of fixed return sukuk type and floating return in Indonesia is quite interesting to obseroe the high returns associated with these and also with the market desire to implement the shariah compliant sukuk. The authors analyze the problem in this paper qualitatively from two perspectives, namely through sharia compliance perspective and the perspective of investment effectiveness. Key words: mudaraba, sukuk, Islamic financial, Islamic banking